Transforming outcome measures in plastic surgery - Harrison, C (2022)
The CLEFT-Q is a patient reported outcome measure (PROM) designed to measure the elements of health most important to people born with a cleft lip or palate (CL/P). Response burden is considered a major barrier to its uptake in routine clinical practice in the UK and abroad. In this thesis, I aimed to develop, validate, and deploy a computerised adaptive testing (CAT) version of the questionnaire, that can provide accurate scores for a respondent, based on an individualised selection of items. This is anticipated to reduce response burden and facilitate the questionnaire’s uptake. I also aimed to explore future research avenues for clinical CAT research, including the quantification of measurement precision, and the application of multidimensional item response theory and regression tree learning.